Vitamin D [25(OH)D] and 1, 25(OH)2D serum concentrations in patients tested at the Charlotte Maxeke Johannesburg Academic Hospital. Issue 2 (4th May 2021) - Botha, S; Maphayi, MR; Cassim, N; George, JA
Abstract : Introduction: There has been a significant increase in vitamin D [25(OH)D] testing in recent years. Aims: To describe the number of tests, concentrations for 25(OH)D and 1, 25(OH)2 D in adults (≥ 18 years), characteristics of those tested and to determine the 25(OH)D concentration at which parathyroid hormone increases (PTH threshold). Methods: Data were extracted for 25(OH)D and 1, 25(OH)2 D tests, from the National Health Laboratory Services data warehouse for Charlotte Maxeke Johannesburg Academic Hospital from 2015 to 2017. Results were categorised by age, sex and race. Vitamin D status was described using National Academy of Medicine guidelines. The PTH threshold was determined by LOWESS plots. Results: 25(OH)D and 1, 25(OH)2 D tests increased, with no change in median concentrations over time. Black Africans (6.7%) had the highest prevalence of Vitamin D deficiency (VDD). Males had significantly lower 25(OH)D values ( p < 0.001) and a higher proportion of VDD ( p = 0.009). Younger patients (< 30 years; 7.9%) and elderly (> 74 years; 10.5%) black Africans had highest prevalence of VDD. The PTH threshold differed by race group. Conclusions: Clear testing guidelines are needed to curb test overutilisation. Further work is required to understand the appropriate cut-off levels to define VDD in our populations.